Posterior Cranial Vault Distraction (PCVD): Common Complication Rates and Strategies of Prevention and Management. Issue 1 (January 2021) - Hassan, Abbas M.; Chappell, Ava G.; Murthy, Nikhil; Stoehr, Jenna R.; Alden, Tord; Gosain, Arun K.
Abstract : Background: Posterior cranial vault distraction (PCVD) is a well-established procedure to treat infants with craniosynostosis. Craniofacial surgeons have seen an evolution in the complications following PCVD. This report aims to demonstrate the rates of common complications from PCVD, and to identify strategies for prevention and management of these complications. Methods: A formal literature review of studies on postoperative complications from PCVD was conducted to identify the breadth of reported complications from PCVD and rates of occurrence. Results: A total of 776 articles were captured by our search strategy. Nineteen original articles met inclusion criteria, with a total of 342 patients. The average rate of reported complications was 25%, range (0%–100%). The most commonly reported complication was postoperative infection (23.7%), followed by cerebrospinal fluid leak (20.3%) and device failure (15.3%). Postoperative infection, device exposure, iatrogenic vascular injury, cerebrospinal fluid leak, and other complications have the potential to disrupt distraction and increase morbidity and mortality. Conclusions: By continuing to identify and evaluate complications, prevention strategies can be determined and standardized to decrease complications from PCVD. These efforts uphold the ultimate goal for surgeons involved in the treatment of craniosynostosis: to provide safe, effective surgical care. Abstract : Supplemental Digital Content is available in the text